2014
DOI: 10.9790/1959-03642126
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Nursing Faculty Members on the Use of Objective Structured Clinical Examinations (OSCE) To Evaluate Competencies

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…A high level of similarity and relevance to actual clinical practice situation had been reported by Mitchell, Henderson [12], which had also found to increase the level of confidence of students. Studies conducted by Salinitri, O'Connell [22] and by Hatamleh and Sabeeb [23] had reported similar results, where OSCE was perceived by the students as highly realistic and relevant to actual clinical practice situations to assess problem-based learning. Use of standardized patients for students' assessment is practiced in some places [24].…”
Section: Discussionmentioning
confidence: 70%
“…A high level of similarity and relevance to actual clinical practice situation had been reported by Mitchell, Henderson [12], which had also found to increase the level of confidence of students. Studies conducted by Salinitri, O'Connell [22] and by Hatamleh and Sabeeb [23] had reported similar results, where OSCE was perceived by the students as highly realistic and relevant to actual clinical practice situations to assess problem-based learning. Use of standardized patients for students' assessment is practiced in some places [24].…”
Section: Discussionmentioning
confidence: 70%
“…Hatamleh et al who reported that in their study also the majority of the respondents were females (85.5%) 13 .…”
Section: Discussionmentioning
confidence: 73%
“…This result shades the light on some challenges faced the faculty in our research which may play crucial role in conducting OSCE properly. The different viewpoint of researchers regarding OSCE makes it difficult to conclude that OSCE is the "Gold standard" for clinical competence assessment (Hatamleh & Abu Sabeeb, 2014) [9] .…”
Section: Discussionmentioning
confidence: 99%
“…To assess challenges affecting quality of OSCEs and suggestions of improvement as perceived by academic nursing staff. [9,6,5,2] . It was used to identify faculty staff perception about challenges experienced during application of OSCE including 2 main challenges.…”
Section: Aim Of the Studymentioning
confidence: 99%